2001
DOI: 10.1007/pl00012013
|View full text |Cite
|
Sign up to set email alerts
|

Indirect interactions mediated by leaf shelters in animal–plant communities

Abstract: Leaf shelters indirectly mediate interactions in animal-plant communities by providing the occupants with several kinds of benefits, as physical ecosystem engineering. The occupants benefit from favorable microhabitat, reduction in antiherbivore defense, and protection from natural enemies. The primary shelter maker has to spend energy and time and producing silk, but shelter users have great advantages without incurring costs. Shelter users consist of a wide range of arthropod taxa and can be divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 76 publications
1
81
1
5
Order By: Relevance
“…Other species modify their surroundings and engineer their own shelters, creating retreats such as nests, burrows, and body coverings (3)(4)(5). The roles of self-made shelters in improving the thermal quality of habitat, reducing desiccation, and concealing predators from their prey are well documented (6,7). Shelters also are frequently assumed to protect against predation (5,6), but this hypothesis is rarely tested.…”
mentioning
confidence: 99%
“…Other species modify their surroundings and engineer their own shelters, creating retreats such as nests, burrows, and body coverings (3)(4)(5). The roles of self-made shelters in improving the thermal quality of habitat, reducing desiccation, and concealing predators from their prey are well documented (6,7). Shelters also are frequently assumed to protect against predation (5,6), but this hypothesis is rarely tested.…”
mentioning
confidence: 99%
“…We also found that A. pisonii fed preferentially on the oldest leaves in the canopy, which contrasts with Wndings from other tropical forests where daily rates of damage were 5-25 times higher on young leaves than on mature leaves (Coley and Barone 1996), presumably due to their higher nutritive values. Although N% and C:N ratios indicated that older R. mangle leaves had much lower nutritional value than younger leaves (Feller et al 2003), the basal position may have been preferred by A. pisonii because it provided a better shelter and a shadier perch, which has been shown to modify the distributions of organisms and inXuence herbivory on some host plants (Fukui 2001).…”
mentioning
confidence: 99%
“…Like many other caterpillars, T. or invests in building a leaf shelter, which provides a more stable microclimate, protection from predators and displacement, and enhanced quality of food (Fukui, 2001). Shelters are also costly, requiring time, energy and material to build (Ruggiero & Merchant, 1986;Fitzgerald et al, 1991;Berenbaum et al, 1993;Cappuccino, 1993;Fitzgerald & Clark, 1994).…”
Section: Do Mandible Scrapes Function In Territorial Behaviour?mentioning
confidence: 99%
“…Leaf shelters are constructed by rolling, folding or tying leaves together with silk, or building webs or tents (Cappuccino, 1993;Lill et al, 2007) and are believed to provide many benefits, including a favorable microclimate, protection from natural enemies and dislodgement, and improved food quality (Fukui, 2001). As such, caterpillars that expend time, energy and material (silk) constructing their own shelters may be expected to defend these valuable commodities from intruding conand heterospecifics.…”
Section: Introductionmentioning
confidence: 99%